Electrochemical sensing of dopamine over polyindole-composite electrode - Pandey P.C.; Chauhan D.S.; Kumari S. (My University, 2025)
We hereby report a new conducting polymer composite i.e., polyindole-camphorsulphonic acid (PIn-CSA) composite, and its use in the development of dopamine sensor. The processable PIn-CSA composite is developed by homogenizing equimolar ratio of chemically synthesized polyindole and camphor sulphonic acid in tetrahydrofuran. The homogenized PIn-CSA composite is cast over the Pt disc electrode under ambient conditions and assembled in a homemade electrode body equipped with Ag/AgCl reference electrode. The ion sensor exhibits excellent response towards dopamine in presence of ascorbic acid over a wide concentration range. The sensor can be used for 1 month without any major drift in its sensitivity and limit of detection.